Efeito da incorporação do trimetafosfato de sódio microparticulado e nanoparticulado ao cimento de ionômero de vidro nas propriedades físico-mecânicas e na desmineralização do esmalte - Abreu, Valéria Marisel de [UNESP] (2015)
The aim of this study was to evaluate the effect of addition of sodium trimetaphosphate (TMP) microparticle (m) and nanoparticle (n) to the glass ionomer cement (GIC) on the physico-mechanical properties and demineralization of the enamel. Specimens (n=54) were fabricated from each experimental group: GIC without TMP (GIC), GIC with 3.5%, 7% and 14% TMPm and GIC with 3.5%, 7% and 14% TMPn. To determine the release of fluoride (F) and TMP it was used six specimens immersed into a demineralization and remineralization solution during 15 days. The physico-mechanical properties evaluated 24 hours and 7 days after fabrication were: compressive strength (n=12), diametral tensile strength (n=12), surface hardness of material (n=6) and the degree of conversion of monomers (n=6). For the study of enamel demineralization, specimens (n=12) were attached to enamel blocks selected by the initial surface hardness test (SH1) and submitted to the pH-cycling. Following, final surface (SH2) and cross-sectional (CSH) hardness, as well as enamel F concentration were determined. Parametric and non-parametric tests were performed after checking the data homoscedasticity (p<0.05). The addition of 14% TMP led to higher mean release of F (p<0.05) and the other groups were similar to the GIC (p>0.05). The release of TMP was higher with 14% microparticulate (p<0.05). The addition of TMP at GIC promoted an average reduction of mechanical properties of 21% (tensile), 10% (compressive) and 18% (hardness) after 24 hours and 18%, 23% and 12% after 7 days. The degree of conversion was lower with addition of 14% TMP compared to the GIC after 24 hours (p<0.05); at 7 days there was no difference between groups (p>0.05). Addition of 7% and 14% TMP reduced mineral loss and increased enamel F concentration when compared...